Emotion Regulation Strategies and Psychological Well-Being in Emerging Adulthood: Mediating Role of Optimism and Self-Esteem in a University Student Sample - Hugo Sanchez-Sanchez; Konstanze Schoeps; Inmaculada Montoya-Castilla (Behavioral Sciences)
Emerging adulthood is a critical phase for emotional development and mental health. Psychological well-being has been associated with using emotion regulation strategies as well as high self-esteem and high optimism. The objective of this study was to examine the mediating role of self-esteem and optimism in the relationship between emotion regulation and psychological well-being in the context of the challenges associated with emerging adulthood. The study was conducted with the participation of 771 university students (M = 20.38, SD = 2.01, 73.3% female), who completed questionnaires, including the Psychological Well-Being Scales (PWBS), the Cognitive Emotion Regulation Questionnaire (CERQ-18), Rosenberg’s Self-Esteem Scale and the Optimism Questionnaire (COP). The results indicate a positive correlation between the adaptive strategies of emotion regulation and the dimensions of psychological well-being, as well as a positive correlation with self-esteem and optimism. A mediation model was tested with an adequate model fit, examining both direct and indirect effects. The model identifies planning, positive reappraisal, and catastrophizing as the most significant emotion regulation strategies, while also emphasizing the importance of some dimensions of well-being, such as self-acceptance, mastery of the environment, and life purpose. Furthermore, the findings illustrate the role of self-esteem and optimism as mediators in these relationships. The study concludes with an analysis of the theoretical and practical implications of the findings in the context of the difficulties associated with emerging adulthood where individuals define their identity, goals and purposes in life and their personality becomes more consistent.